Integrating Sustainable Development and Disaster Mitigation into Climate Policies to Support Water Security in Africa - Sola Ojo; Solomon Asamoah; Eike Albrecht; Bachar Ibrahim (Earth, 2025)
Africa’s water security is inextricable from the recent patterns of climate variability. Effective formulation and implementation of climate policies require efficient integration of disaster mitigation and sustainable development to eliminate maladaptation and enhance water security. However, practical implementation is still lacking in many African countries. This study aims to examine practical measures and strategies for the integration of sustainable development and disaster mitigation into climate policies to enhance water security in Africa. A systematic bibliometric and thematic analysis was conducted using 95 peer-reviewed articles within the period 2010 to 2025 from the Scopus database. Software and frameworks such as VOSviewer and the Preferred Reporting Items for Systematic Reviews (PRISMA) were employed to analyze publication trends, co-authorship networks, keyword co-occurrence, and themes. The study revealed current research themes such as nature-based solutions for water security, climate-resilient infrastructure and technologies, and practical measures, such as eco-based adaptation and water energy food nexus, as some components of climate policy integration that can enhance water security in Africa. The study offers key policy recommendations for policymakers in the implementation of integrated climate policies adequate and effective enough to deal with water security issues in Africa.